Informal work in sub-Saharan Africa: Dead end or stepping-stone? - Michael Danquah; Simone Schotte; Kunal Sen (IZA Journal of Development and Migration, 2021)
Despite rapid economic growth in recent decades, informality remains a persistent phenomenon in the labor markets of many low- and middle-income countries. A key issue in this regard concerns the extent to which informality itself is a persistent state. Using panel data from Ghana, South Africa, Tanzania, and Uganda, this paper presents one of the very few analyses providing evidence on this question in the context of sub-Saharan Africa. Our results reveal an important extent of heterogeneity in the transition patterns observed for workers in upper-tier versus lower-tier informality. Given the limited alternative job opportunities available, particularly to those in lower-tier informal self-employment who often remain locked in a situation of inferior pay and conditions, specific policies that seek to enhance the livelihoods of workers in this most disadvantaged segment may be more relevant in the sub-Saharan context than policies that aim to reduce the regulatory barriers to formalization.
Keywords: D31; J46; J62; O12; 330; informality; segmentation; labor market dynamics; sub-Saharan Africa